Pengaruh Implementasi Customer Relationship Management, Layanan Prioritas dan Mobile Banking terhadap Loyalitas Nasabah Prioritas di Bank Sinarmas Kantor Cabang Thamrin Jakarta Pusat - Cahyadi, Hendro (Lembaga Yasin AlSys, 2026)
Customer loyalty is an important indicator of banking business success amid increasingly intense industry competition, particularly in urban areas such as Central Jakarta. This study aims to empirically analyze and test the partial and simultaneous effects of the implementation of Customer Relationship Management (CRM), priority services, and mobile banking on customer loyalty at Bank Sinarmas Thamrin Branch Office, Central Jakarta. This study used a quantitative approach with a causality design. Data were collected through questionnaires distributed to 65 priority customers of Bank Sinarmas Thamrin Branch Office, Central Jakarta, who were selected using purposive sampling. The data were analyzed using multiple linear regression. The results showed that, partially, CRM implementation had a positive and significant effect on customer loyalty, indicating that personalized customer relationship management can strengthen loyalty. Priority services also had a positive and significant effect on customer loyalty, thereby emphasizing the importance of exclusive services in retaining premium customers. In addition, mobile banking had a positive and significant effect on customer loyalty, indicating that the ease and accessibility of digital transactions are important factors in the customer experience. Simultaneously, CRM implementation, priority services, and mobile banking had a significant effect on customer loyalty at Bank Sinarmas Thamrin Branch Office. The conclusion of this study affirms that strengthening CRM, improving the quality of priority services, and optimizing the mobile banking platform play important roles in building sustainable customer loyalty. These findings imply the need for Bank Sinarmas to improve CRM system integration, strengthen priority service facilities, and ensure the stability and ease of use of digital services to maintain long-term customer loyalty.